2020
DOI: 10.1097/der.0000000000000702
|View full text |Cite
|
Sign up to set email alerts
|

Contact Dermatitis From Gum Mastic (Pistacia lentiscus) and Gum Storax (Liquidambar styraciflua) in Mastisol-Allergic Patients

Abstract: Background: Mastisol Liquid Adhesive is widely used on the skin, especially after surgical procedures. It contains gum mastic, gum storax, methyl salicylate, and ethanol.Objective: The aims of the study were to review our experience patch testing patients allergic to Mastisol and to assess coreacting substances.Methods: We identified 18 patients who were allergic to Mastisol. Most of these had a history of postoperative or cardiac electrode dermatitis and underwent patch testing with multiple surgically relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…We further hypothesize that elements in various types of medical adhesives may have led to MARSI such as latex particles that may create a hypersensitivity response manifested as irritant contact dermatitis and formation of blisters. 3,[15][16][17] Nutritional status of patients has been postulated to influence the risk for MARSI and we found that patients who developed MARSI were more likely to require TPN for nutritional support. 18,19 In addition to these factors, the choice of medical adhesive device, duration of its use, and techniques for applying and removing tapes influence the likelihood of MARSI.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…We further hypothesize that elements in various types of medical adhesives may have led to MARSI such as latex particles that may create a hypersensitivity response manifested as irritant contact dermatitis and formation of blisters. 3,[15][16][17] Nutritional status of patients has been postulated to influence the risk for MARSI and we found that patients who developed MARSI were more likely to require TPN for nutritional support. 18,19 In addition to these factors, the choice of medical adhesive device, duration of its use, and techniques for applying and removing tapes influence the likelihood of MARSI.…”
Section: Discussionmentioning
confidence: 65%
“…We also found that a higher proportion of patients who developed MARSI had a history and positive skin scratch tests (8.9% vs 3.0%). We further hypothesize that elements in various types of medical adhesives may have led to MARSI such as latex particles that may create a hypersensitivity response manifested as irritant contact dermatitis and formation of blisters 3,15–17. Nutritional status of patients has been postulated to influence the risk for MARSI and we found that patients who developed MARSI were more likely to require TPN for nutritional support 18,19.…”
Section: Discussionmentioning
confidence: 70%
“…Mastic gum consumption is generally considered safe, although the long-term safety has not been sufficiently investigated, and the maximum safe dose remains still unknown. Beyond some cases of allergic contact dermatitis following postoperative use of patches containing mastic, there are hardly any reports of remarkable side effects [56]. High doses of mastic have also been well tolerated in clinical trials, and no adverse effects have been recorded.…”
Section: Adverse Effects-toxicitymentioning
confidence: 99%